Hubungan Pekerjaan Orang Tua dan Asi Eksklusif dengan Kejadian Stunting Di Menawi Kabupaten Kepulauan Yapen - Lindawati Lindawati; Alprida Harahap; Anto Anto (Journal of Pharmaceutical and Health Research, 2023)
Indonesia has a fairly severe nutritional problem, which is marked by the many cases of stunting in children under five. This study aims to analyze social relations. Demographics and behavior of nutrition-aware families and the incidence of stunting in the working area of the Menawi Nursing Health Center, Yapen Islands District This is an observational study with a cross-sectional approach.The population is all families with 242 toddlers and a sample of 149 toddlers in the Menawi Nursing Health Center, Yapen Islands Regency, using purposive sampling and statistical tests using chi-square and logistic regression. The research results showed that occupation (p = 0.018), contact with other cultures (p = 0.001), exclusive breastfeeding (p = 0.001), consumption of diverse foods (p = 0.001), and family behavior aware of nutrition (p = 0.001) were variables related to stunting, while education (p = 0.394) and income (p = 0.646) were not related to stunting. In addition, the behavior of the family that is aware of nutrition has the most influence on the incidence of stunting, with a value of Exp (B) = 3.884. The conclusion obtained is that work, contact with other cultures, exclusive breastfeeding, consumption of a variety of foods, and family behavior that is aware of nutrition are factors that cause stunting. So that sustainable health interventions are needed in the form of family nutrition education.